Paradigmatic Analysis and the Performance of Xenakis’s Solo Percussion Music - Marandola, Fabrice (Revue musicale OICRM, 2025)
This article explores the application of paradigmatic analysis as a practical tool for performers to deepen their understanding and interpretation of Iannis Xenakis’s solo percussion works, particularly Psappha (1975) and Rebonds (1987-1989). Drawing from personal experience and analytical methods developed by Nicolas Ruwet and Simha Arom, I demonstrate how segmenting musical material based on repetition and marks such as accentuation, timbre, and durations can enhance the learning process and inform interpretative decisions. The study emphasizes the value of performer-driven analysis in navigating Xenakis’s complex rhythmic and structural designs. Through detailed examples, I illustrate how paradigmatic analysis can reveal underlying patterns, support memory retention, and inspire creative performance strategies. Ultimately, I advocate for a flexible, evolving analytical practice that aligns with the interpretive needs of musicians engaging with contemporary percussion repertoire.